A Family of Related Fungal and Bacterial Di‐ and Sesterterpenes: Studies on Fusaterpenol and Variediene. (7th November 2019) - Rinkel, Jan; Steiner, Simon T.; Bian, Guangkai; Chen, Rong; Liu, Tiangang; Dickschat, Jeroen S.
Abstract: The absolute configuration of fusaterpenol (GJ1012E) has been revised by an enantioselective deuteration strategy. A bifunctional enzyme with a terpene synthase and a prenyltransferase domain from Aspergillus brasiliensis was characterised as variediene synthase, and the absolute configuration of its product was elucidated. The uniform absolute configurations of these and structurally related di‐ and sesterterpenes together with a common stereochemical course for the geminal methyl groups of GGPP unravel a similar conformational fold of the substrate in the active sites of the terpene synthases. For variediene, a thermal reaction observed during GC/MS analysis was studied in detail for which a surprising mechanism was uncovered. Abstract : Absolute configuration of fusaterpenol (GJ1012E) revised : Variediene isolated from a newly characterised fungal diterpene synthase has a related absolute configuration. The comparison to other known diterpenes and labelling experiments point to a common substrate fold for a family of related compounds. A thermal reaction of variediene observed during GC/MS analysis is studied in detail.